Exotic Pine Trials in Uttar Pradth - Chaturvedi, A. N.; Dwivedi, B. N. (Indian Forester, 1982)
Trials of exotic pines were started in U.P., from 1960-61 onwards. Field trials laid at various places and at different elevations have indicated that Pinus patula, Pinus greggll, Pinus pseudo-strobus and Pinus montezumae when planted in the deep moist soils at an elevation ranging between 1800 to 2000 m. grow faster than local chir pine in early stage upto 15 years age. Pinus elliottii and Pinus taeda come up even on skeleton soils between 1200 to 1500 m but survival is poor. In the nurseries seed is sown on pure sand and pricking is generally done 15-20 days after germination. The pricking is done in polythene bags of size 15 cm × 22.5 cm of 150 gauge. Mycorrhizal soil is added to the potting mixture and also after about a week in the bag plants. Spraying of 0.25% to O.33% of Aaromine or 1-2g of Sufla or D.A.P. and 2-3 g of superphosphate boosts the height growth of seedings significantly. In the field plantings plants of 20-25 cm height are used. Pit size 45 cm3 has given the best results and is adopted for field plantations. Spacing is kept 1 m × 2 m or 3 m × 3 m. Most of the exotic pines start bearing cones at 5-6 years age And produce mature seeds after 9-10 years. The viability of seed varies from l5-30% in cose of Pinus patula and Pinus greggii. Micro-tapping done in very limited number of plants of 13 species has indicated that Pinus elliottii gives satisfactory resin yield while in Pinus potula and Pinus greggii yield is poor. In nurseries seedlings are sometimes killed by Cercospora, Fusarium and other fungi. In the field an attack of Diplodia pinea has been noticed at several places. This results in die-back and top drying of plants. In several Cases plants become bushy. Mild incidence of Lophodermium fungus has also been noticed. Localized damage to the plants from Chafer grub, bag worms and termites has also been noticed. Though the field plantations of exotic pines are very recent and stage of harvesting has not yet been reached, their potential use can be for long fibred pulp, for transmission poles after proper prophylactic treatment and in manufacture of paper by thermo-mechanical process. Encouraged by the performance of some of the exotic pines, demonstration field trials were started in 1975 with the co-operation of local Divisional Forest Officers. Since 1979 about a lakh of plants of various exotic pines are being planted every year. It is proposed to further increase to own lakh plants from 1982 rains and four lakh plants in 1984.